FIRE PROTECTION PROPERTIES OF WOOD IN WATERBORNE EPOXY COATINGS CONTAINING FUNCTIONALIZED GRAPHENE OXIDE. (3rd September 2019) - Chen, Xuexi; Li, Junfei; Gao, Ming; Yue, Lina; Zhou, Xuan
Abstract : Functionalized graphene oxide (FGO) modified by H3 BO3 and (C2 H5 O)3 –Si–(CH2 )3 NH2 was prepared and applied as an intumescent flame retardant (IFR) coating to reduce thermal transmission to a substrate and enhance fire resistance. Its structural features were tested using Fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD), and energy-dispersive X-ray spectrometry (EDS). The IFR coating presented here is based on melamine pyrophosphate (MPP), pentaerythritol (PER), and melamine-formaldehyde resin (MF), with waterborne epoxy resin (WEP) used as an adhesive. The flame retardancy of the coatings was tested on a small scale using the "big panel method" and cone calorimeter test (CCT). The coatings structure and thermostability were investigated using thermogravimetric analysis (TGA), and scanning electron microscopy (SEM), respectively. The results show that the addition of 0.083 phr FGO into the IFR system provided effective fire protection. The SEM results show that the char residues have better morphology, height, and structure, making them useful as a protective shield. Significantly, the IFR coating containing 0.05 g of FGO has proved effective in protecting plywood from fire.